Effect Of Plant Biomass Harvesting On Waste Nutrient Removal From Fish Farm Wastewater - Farid, Durrah Faiqah Mohd (Universiti Sains Malaysia, 2017)
The main purpose of this work is to study the effect of plant biomass harvesting on waste nutrient removal from fish farm wastewater using Lemna and Spirodela sp. The effect of biomass harvesting on the performance of Lemna and Spirodela sp. in the nutrient removal from fish farm wastewater was evaluated in feed batch processes. The experiment was conducted for 14 days and the water samples to be tested were collected for every 2 days. The initial weight of both sp. in every container is 4.2 g. The performance of Lemna and Spirodela were determined by six tests which were nitrate, phosphate, turbidity, ammonia, chemical oxygen demand (COD) and mixed liquor volatile suspended solids (MLVSS) tests. The nitrate concentration increases the highest at 1.7 mg/L NO3--N without the presence of Lemna and Spirodela sp. The concentration of phosphate in the water sample greatly reduced to 0.04 mg/L PO43- on day 14 which the last day of the experiment in the harvested Spirodela batch. A decreasing trend is obtained in turbidity for all water samples but the decrease is faster with the presence of Lemna and Spirodela. The concentration of ammonia reached 0 mg/L N the fastest with Spirodela sp. which is on day 6 while day 10 and day 12 for Lemna and without duckweed respectively. The COD level reached 0 mg/L O2 the fastest with Lemna sp. without harvesting. The MLVSS increased greatly with the presence of Lemna and Spirodela sp.